PEMANFAATAN LIMBAH SABUT KELAPA (Cocos nucifera L.) SEBAGAI KOMPOS DENGAN MENGGUNAKAN BIOAKTIVATOR EM4 - Daryono Daryono; Rusmini Rusmini; Yuanita; Nur hidayat; Riama Rita Manullang; Arief Rahman; Rusli Anwar; Anis Syauqi (JURNAL AGRIMENT, 2022)
This The background of this research is waste from coco coir with bioactivator EM4, the manufacture of solid fertilizer utilizing waste from coco coir that is not treated properly has quite an impact on environmental pollution. Solid organic fertilizer is the decomposition of organic matter by a complex compound reform process with the help of microorganisms. The purpose of this study was to measure the time of making solid organic fertilizer, to analyze the nutrient content of N, P, K, C-organic, C/N ratio and pH. The research was conducted on Jl. Samratulangi ex. Gunung Panjang, Kec. Keledang River, East Kalimantan Province. This research lasts for 2 months from January to February 2021. The results of the study, the length of time in the P1 fertilizer treatment was finished on the 16th day while the P2 fertilizer had been finished on the 21st day. Analysis of the nutrient content in the P1 treatment was N total 0.084% , P total 0.0301%, K total of 0.03994 % , C/N ratio was 52.10, and P2 treatment, namely N total 0.098 %, P total 0.0403 %, K total 0.06534 %, C/N ratio 45.9, did not meet the Quality Standards of the Regulation of the Minister of Agriculture of the compost requirements number 261/Permentan/ SR.310/4/2019, while the total P1 C-organic content was 0.44,512 %, pH was 5.38 and P2 C-organic total was 45.032 %, pH 5.74 already meets the Quality Standards of the Regulation of the Minister of Agriculture for compost requirements number 261/Permentan/SR.310/4/2019